PENERAPAN PERATURAN KAPOLRI NOMOR 11 TAHUN 2010 TENTANG PENANGANAN PENJINAKAN BOM - Moonti, Roy; Kadir, Yusrianto; Bunga, Marten; Ahmad, Ibrahim; Koni, Yoslan K. (IBLAM LAW REVIEW, 2022)
The purpose of this research is to determine the effectiveness implementation regulation of the chief of Indonesian national police 11 of 2010 regarding the handling of bomb disposal and to find out what factors influenced bomb disposal procedures in Gorontalo Province. The type of research used in this research is empirical normative legal research. The type of research used is empirical normative legal research. Normative law research uses normative legal case studies in the form of legal products, for example reviewing draft laws. The subject of the research is the law which is conceptualized as a norm or rule that applies in society and becomes a reference for everyone. Empirical legal research is research that uses empirical legal case studies in the form of community behavior. The results of the research obtained are that regulation of the chief of Indonesian national police number 11 of 2010 concerning the handling of bomb disposal in Gorontalo Province has not been effective because it was found that there are still several aspects that are not following the provisions in regulation of the chief of Indonesian national police, for example, related to personnel standardization, individual equipment is not adequate, Some of the new unit equipment are complete and some are damaged, then spare parts are not ,available as well as administrative processes that are often ignored and the factors that affect the bomb disposal procedure in Gorontalo province, namely inadequate facilities and infrastructure, incomplete personnel / human resources, insufficient budget and no insurance for each Jibom personnel.